Debt diplomacy in the 1920s: The case of the French and Hellenic war debts - Vincent Carretta (Duke University, Center for the History of Political Economy (CHOPE), 2022)
In the aftermath of World War I, a financial war was fought on the battlegrounds of international organizations and financial diplomacy. While the League of Nations' Economic and Financial Organization tried to ensure the reconstruction of Europe through guaranteed loans and financial reforms, the Great Powers who dominated the League tried to maintain their spheres of influence. The case of the French-Hellenic war debts illustrates those issues: in the 1920s, the Greeks were barred from international capital markets after years of wars and financial mismanagement. A mission was sent to Greece by the League to evaluate the reforms needed before backing the emission of a loan, with several French emissaries among the envoys. The French government subsequently tried to take advantage of the ratification process of the loan, by threatening to block its emission if the Greeks did not repay their war debts. The debt-diplomacy of the French government is an example of a two-level game: pushed to the brink on the domestic side by their own financial troubles and resentment over the German reparations, France sought to obtain an international victory through the process of European reconstruction. On the international scene, they were stymied by the extension of Anglo-American financial interests. The political process of the League shows how much economic problems were subordinate to political considerations, and how domestic and international levels were entangled in the financial diplomacy of the postwar reconstruction.
Keywords: F34; N24; N44; B31; 330; War Debts; 1920s; League of Nations; Jacques Rueff; France; Greece